European Commission initiatives to promote the general interest of the European Union - Ioana Nely MILITARU; Adriana MOŢATU (Juridical Tribune, 2014)
Each institution of the Union has an interest in it. In this context, the Commission is also namely, that of the Union, initially of the European Communities, thereby explaining – and is pronounced supranational character of the institution. Representing the Union’s general interest is reflected by Treaties. This paper presents the Commission’s initiatives appropriate its functions to support the Union’s general interest.